Resultados del uso de geodesia satelital para estudios geodinámicos en Colombia - Mora-Páez Hector; Trenkamp Robert; Kellogg James; Freymueller Jeff; Droonez-Villota Milton (Earth Sciences Research Journal)
The use of GPS technology provides direct measurements of displacements due to plate motions and intraplate deformation, basic information for understanding kinematic of the movements. Using satelital geodesy techniques, crustal deformation rates in the southwestern Caribbean, southeastern of Central America and northwestern of South America wide plate boundary have been derived from GPS campaigns in 1988, 1990, 1991, 1994, 1996 and 1998 as part of the CASA (Central And South America) GPS Project. The zone of study includes the area of complex interaction between the Caribbean, Nazca and South America plates. The same GPS stations have been occupied with the purpose of making comparisons on the position of each site, analyzing distances of separation (baselines) and obtaining displacement vectors (magnitude and orientation). Some results are showed using the GIPSY -OASIS II software, that is a precision package for the analysis of GPS data developed by JPL-NASA. INGEOMINAS has built a GPS network called GEORED to be occupied succesively in order to get information about intraplate deformation, under the institutional project named Survey, Compilation and Generation of Geodynamics Information. EI uso de la tecnología GPS provee mediciones directas de los desplazamientos debido al movimiento de las placas y la deformación intraplaca, información básica para el entendimiento de la cinemática de los movimientos, Empleando técnicas de geodesia satelital, tasas de deformación de corteza terrestre en el límite amplio de placas al suroeste del Caribe, sureste de América Central y noroeste de Suramérica han sido derivadas de las campañas de GPS efectuadas en 1988, 1990, 1991, 1994, 1996 y 1998 como parte del proyecto de GPS denominado CASA. (Central And South América). La zona de estudio comprende el área de compleja interacción de las placas Caribe, Nazca y Suramérica, Las mismas estaciones GPS han sido ocupadas con el propósito de hacer comparaciones en la posición de cada sitio, analizando distancias de separación (líneas base) y obteniendo vectores de desplazamientos (magnitud y orientación). Se muestran algunos resultados obtenidos usando el software GIPSY -OASIS II, un paquete de precisión para el análisis de datos GPS, desarrollado par JPL-NASA. Ingeominas ha establecido en Colombia una red de estaciones GPS, denominada GEORED, para efectuar ocupaciones sucesivas y obtener información de deformación intraplaca, bajo el proyecto institucional denominado Levantamiento, Compilación y Generación de Informacion de Informacion Geodinámica.